Effects of Unilateral Stimulation in Parkinson's Disease: A Randomized Double-Blind Crossover Trial - Zeng, Zhitong; Wang, Linbin; Shi, Weikun; Xu, Lu; Lin, Zhengyu; Xu, Xinmeng; Huang, Peng; Pan, Yixin; Chen, Zhonglue; Ling, Yun; Ren, Kang; Zhang, Chencheng; et al. (Frontiers in Neurology, 2022)
Introduction: Previous studies have shown that subthalamic nucleus (STN) and unilateral globus pallidus interna (GPi) are similarly effective in the deep brain stimulation (DBS) treatment of motor symptoms. However, the counterintuitively more common clinical application of STN DBS makes us hypothesize that STN is superior to GPi in the treatment of motor symptoms. Methods: In this prospective, double-blind, randomized crossover study, idiopathic PD patients treated with combined unilateral STN and contralateral GPi DBS (STN in one brain hemisphere and GPi in the other) for 2 to 3 years were enrolled. The MDS UPDRS-III total score and subscale scores for axial and bilateral limb symptoms were assessed preoperatively and at 2- to 3-year follow-up in four randomized, double-blinded conditions: 1) Med−STN+GPi−, 2) Med−STN−GPi+, 3) Med+STN+GPi−, and 4) Med+STN−GPi+. Results: Eight patients had completed 30 trials of assessment. Compared with the preoperative Med− state, in the Med−STN+GPi− condition, the cardinal symptoms in both sides of the body were all improved. In the Med−STN−GPi+ condition, symptoms of the GPi-stim limb were improved, while only tremor was improved on the ipsilateral side, although all axial symptoms showed aggravation. Compared with the preoperative Med+ state, in the Med+STN+GPi− state, cardinal symptoms were improved on both sides, except that tremor was worsened on the STN-stim side. In the Med+STN−GPi+ state, the overall motor symptoms were aggravated compared with the preoperative Med+ state. Most axial symptoms worsened at acute unilateral STN or GPi DBS onset, compared to both preoperative Med− and Med+ states. No side effects associated with this study were seen. Conclusions: Improvement in motor symptoms was significantly greater in all sub-scores favoring STN. The effects of STN+ were seen on both sides of the body, while GPi+ mainly acted on the contralateral side.